Ovicidal activity of different concentrations of Pochonia chlamydosporia chlamydospores on Taenia taeniaeformis eggs - Braga, F.R.; Silva, A.R.; Carvalho, R.O.; Araújo, J.V.; Pinto, P.S.A. (Journal of Helminthology, 2010)
Three concentrations of chlamydospores of the nematophagous fungus Pochonia chlamydosporia (1000, 10,000 and 20,000 per Petri dish) were evaluated in vitro on Taenia taeniaeformis eggs. Chlamydospores at each concentration were cultured in two different media: 2% water-agar (2%WA) and 2% corn-meal-agar (2%CMA). Taenia taeniaeformis eggs were plated in each chlamydospore concentration in 2%WA and 2%CMA (treated groups) and without fungus (control group). Eggs were removed from each Petri dish at intervals of 7, 14 and 21 days and classified according to ovicidal activity (type 1, type 2 and type 3 effects). Plates containing 2%CMA showed the highest percentages for type 3 effect (81.3%) on the 21st day of observation. A difference (P , 0.01) between the media 2%WA and 2%CMA for type 1 effect was observed only at a concentration of 1000 chlamydospores on the 7th day. There were differences (P , 0.01) between 2%WA and 2%CMA on the 14th and 21st days, at the concentration of 20,000 chlamydospores, for type 1 and type 3 effects. Regression curves for type 3 effect in 2%WA and 2%CMA at the tested concentrations showed higher ovicidal activity with increasing chlamydospore concentrations. Results indicate that, at concentrations of 1000, 10,000 and 20,000 per Petri dish, chlamydospores of P. chlamydosporia effectively destroyed T. taeniaeformis eggs and can be considered a potential biological control agent for this cestode.
Keywords: Ovicidal activity; Pochonia chlamydosporia chlamydospores; Taenia taeniaeformis eggs